2021
DOI: 10.14814/phy2.14835
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of K Ca 2.1 ( KCNN1 ) K + channel expression by histone deacetylases in atrial fibrillation with concomitant heart failure

Abstract: Atrial fibrillation (AF) with concomitant heart failure (HF) poses a significant therapeutic challenge. Mechanism‐based approaches may optimize AF therapy. Small‐conductance, calcium‐activated K+ (KCa, KCNN) channels contribute to cardiac action potential repolarization. KCNN1 exhibits predominant atrial expression and is downregulated in chronic AF patients with preserved cardiac function. Epigenetic regulation is suggested by AF suppression following histone deacetylase (HDAC) inhibition. We hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Previous protein analyses were confined to animals studied after 14 days atrial burst pacing due to limited sample availability and indicated a tendency towards decreased K Ca 2.1 protein expression in RA tissue. 18 Furthermore, reduced expression of the right atrial K Ca 2.2 and K Ca 2.3 protein after 14 days AF in pigs has been reported previously. 16 Tachypacing-Related Remodeling of K Ca 2…”
Section: Dovepressmentioning
confidence: 53%
See 4 more Smart Citations
“…Previous protein analyses were confined to animals studied after 14 days atrial burst pacing due to limited sample availability and indicated a tendency towards decreased K Ca 2.1 protein expression in RA tissue. 18 Furthermore, reduced expression of the right atrial K Ca 2.2 and K Ca 2.3 protein after 14 days AF in pigs has been reported previously. 16 Tachypacing-Related Remodeling of K Ca 2…”
Section: Dovepressmentioning
confidence: 53%
“…Paroxysmal AF was associated with reduced expression of KCNN1 (−73%, n = 10, P = 0.010), KCNN2 (−62%, n = 10, P = 0.010), and KCNN3 (−50%, n = 10, P = 0.003) compared to HF patients with SR (n = 10) (Figure 1C), as reported earlier. 16,18 In HF patients with cAF, KCNN expression was similarly suppressed by 78% (KCNN1, n = 10, P < 0.0001), 55% (KCNN2, n = 10, P = 0.010), and 48% (KCNN3, n = 10, P= 0.037), respectively (Figure 1C). 16,18 K Ca 2 Channel Remodeling in a Porcine AF/HF Model…”
Section: Af-related K Ca 2 Channel Remodeling In Hf Patientsmentioning
confidence: 92%
See 3 more Smart Citations